Cumulative Violence and PTSD Symptom Severity Among Urban Street-Based Female Sex Workers - Park, Ju Nyeong (Journal of interpersonal violence, 2021)
Female sex workers (FSW) are a marginalized and vulnerable population at high risk of gender-based violence within and outside of their occupation. However, FSW remain underrepresented in the trauma and mental health literature. The aims of this study were to (a) characterize exposure to violence among street-based FSW, including violence type, patterns over the life course, and key perpetrator groups, and (b) examine the multivariate associations between posttraumatic stress disorder (PTSD) symptom severity and two constructs (revictimization across life stages and cumulative violence). Data were drawn from the Sex Workers and Police Promoting Health in Risky Environments (SAPPHIRE) study, an observational community-based cohort of street-based FSW recruited through targeted sampling across Baltimore, Maryland (USA) in 2016 to 2017. PTSD symptom severity was measured using the PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders–Fifth Edition (PCL-5). At baseline, 61% of FSW screened positive for PTSD symptoms. The mean PCL-5 score was 38.6. We documented extensive histories of sexual and physical violence (lifetime: 81.8%; childhood and adult revictimization: 15.0% for sexual and 37.7% for physical). The vast majority of perpetrators were male and included paying clients, police officers, family members, and intimate partners. Exposure to childhood and adult sexual violence were independently associated with higher PTSD severity (p < .05), with marginal associations observed for physical violence. Data supported a cumulative violence model of PTSD severity (p < .05). Binge drinking also appeared to be a contributing factor (p < .05). The levels of PTSD observed among our sample were comparable with that reported among treatment-seeking war veterans. Our findings underscore the urgent need for tailored trauma-informed interventions and policies to address violence among urban street-based FSW, a population experiencing extremely high levels of violence, PTSD, and substance use.